Variation Characteristics in Growth Stages of Winter Wheat (Triticum Aestivum L.) And Prediction Model (Bangladesh Journal of Botany, 2021)
The variation characteristics of growth stages of winter wheat (Triticum aestivum L.) with the climate change were measured by designing its stability and prediction model. Results showed the trend of stability of growth stage of winter wheat in Jiangsu province of China was an S-shaped curve indicating the growth of winter wheat was more stable in late stage. The lengths of early and late stages of growth were in inverse proportion. Specifically, when the early stage was prolonged, the late stage was shortened, which ensured the relative stability of the length of growth stage. The length of growth stage was correlated with the meteorological conditions. Thus, favorable meteorological conditions contributed to the stability of growth stages of winter wheat. Along with the climate change, the basic statistical characteristics of growth stage remained stable. Each stage drifted moderately under the variation of meteorological conditions, typically during the stage of vegetative growth. The growth process can be regulated by means of variety improvement, adjustment of sowing time and density, reasonable fertilization, and the use of growth regulators. These measures are able to counteract the influences of climate change on winter wheat production and ensure the production security.Bangladesh J. Bot. 50(3): 737-746, 2021 (September) Special